Analisis Human Error Menggunakan Metode SHERPA Dan HEART Pada Proyek Rumah Tinggal - Restu Maulana Nashuha; Jody Martin Ginting (LPPM Universitas Abdurrab, 2026)
The construction industry has a high rate of workplace accidents, with most incidents caused by human error. This study aims to analyze the potential for human error in residential construction projects using the Systematic Human Error Reduction and Prediction Approach (SHERPA) and Human Error Assessment and Reduction Technique (HEART) methods. This study applies a quantitative approach by obtaining primary data through observation and interviews, and collecting secondary data from relevant project documents. The SHERPA method is used to identify types of errors based on work task analysis, while the HEART method is used to calculate the probability of human error (Human Error Probability/HEP) by considering the Error Producing Conditions (EPC). The analysis results show that the formwork installation task on foundations and columns has the highest HEP value, namely 0.256, followed by the work of creating boundary lines for wall installation with an HEP of 0.1332. Recommendations provided include technical training outside operating hours and increased work supervision. The integration of the SHERPA and HEART methods has proven effective in producing comprehensive risk evaluations and supporting systematic human error mitigation efforts in the construction field.